Clinician Perspectives on Barriers and Facilitators to Implementing e-Health Technology in Substance Use Disorder (SUD) Treatment Facilities. (November 2021) - Fleddermann, Kathryn; Molfenter, Todd; Jacobson, Nora; Horst, Julie; Roosa, Mathew R; Boss, Deanne; Ross, J Charles; Preuss, Eric; Gustafson, David H
Background: Substance use disorders (SUDs) in the United States cause many preventable deaths each year. Finding effective ways to manage SUDs is vital to improving outcomes for individuals seeking treatment. This has increased interest in using e-health technologies in behavioral healthcare settings. This research is part of a larger study evaluating the efficacy of the NIATx coaching intervention for implementing RISE Iowa, an e-health patient recovery app, in SUD treatment organizations and seeks to examine clinician perspectives of the barriers and facilitators to its implementation. Method: Semi-structured qualitative interviews were conducted with 13 clinicians from 9 different intervention sites involved in the study. Results: Major barriers to implementing e-health technology include inability to access the technology, lack of time for both patients and clinicians, and a perceived lack of patient motivation to make changes. Facilitators to implementation include collaboration with other staff using e-health technology and integrating technology use into typical workflows. Conclusions: Implementation of e-health technology in SUD treatment will require integrating the technology into clinical workflows and improving patient access to the technology.